Fabrication of hierarchical iron-containing MnO2 hollow microspheres assembled by thickness-tunable nanosheets for efficient phosphate removal. Issue 38 (15th September 2016) - Ge, Xiao; Song, Xiangyang; Ma, Yue; Zhou, Hongjian; Wang, Guozhong; Zhang, Haimin; Zhang, Yunxia; Zhao, Huijun; Wong, Po Keung
Abstract : Hierarchical flower-like iron containing γ-MnO2 hollow microspheres assembled by thickness-tunable nanosheets have been successfully fabricated, demonstrating the morphology-dependent phosphate removal performance. Abstract : The eutrophication of water bodies caused by the excessive release of phosphorus is becoming a serious world-wide environmental problem. To address this issue, the exploitation of three-dimensional (3D) hierarchical architectures will be an effective strategy for sequestrating phosphate and preventing the occurrence of eutrophication. In this study, 3D flower-like hierarchical iron containing MnO2 hollow microspheres have been successfully fabricated via a facile one-step template-free route for the efficient removal of phosphate. Field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) studies show that the microspheres obtained consist of numerous intertwining nanosheets. Strikingly, the thickness of these nanosheets can be elaborately modulated ranging from 30 to 2 nm via varying Fe/Mn ratios, accordingly resulting in variation in the resultant phosphate adsorption performance. The uptake of phosphate onto these hierarchical microspheres shows that the obtained hierarchical iron containing MnO2 hollow microspheres possess markedly enhanced phosphate removal performance over undoped counterparts regardless of the removal rate or efficiency; meanwhile, the enhanced effect becomes more obvious with increasing iron amount due to the larger specific surface area and abundant active sites. In particular, the hierarchical MnO2 microspheres with 15 at% Fe incorporation are capable of removing completely low concentration phosphate (below 10 ppm) at a dosage of 0.5 g L −1 . In addition, the as-obtained materials exhibit high sorption selectivity toward phosphate over other coexisting ions or dissolved organic matter (DOC) at high levels, which can be ascribed to the unique hierarchical structures and strong interaction between Mn/Fe sites and phosphate, as confirmed by Fourier-transform infrared (FT-IR) and X-ray photoelectron spectroscopy (XPS) analyses. Furthermore, the regenerated materials can be repeatedly used for five cycles without obvious degradation of performance, suggesting the sustainability of the adsorbents. By virtue of the high removal efficiency, fast adsorption kinetics, preferable sorption selectivity, as well as satisfactory recyclability, the obtained hierarchical iron containing MnO2 hollow microspheres will be promising in eliminating the phosphate pollution from eutrophic waters.